Evaluation of ribotyping for characterization and identification of Enterococcus haemoperoxidus and Enterococcus moraviensis strains - Svec, P; Sedlácek, I; Pantůcek, R; Devriese, L A; Doskar, J V (FEMS microbiology letters, 2001)
Seven Enterococcus moraviensis and 16 Enterococcus haemoperoxidus as well as nine reference cultures of other enterococcal species obtained from the Czech Collection of Microorganisms were characterized using ribotyping with EcoRI and HindIII in the present work. The ribopatterns obtained by both restriction enzymes clearly distinguished all E. moraviensis and E. haemoperoxidus strains from the other enterococci (E. faecalis, E. faecium, E. avium, E. raffinosus, E. pseudoavium, E. malodoratus) and they differentiated both species from each other as well. Although all strains were isolated from different sampling sites, many strains shared the same band patterns. E. moraviensis formed four ribogroups using EcoRI and two ribogroups using HindIII restriction enzyme. E. haemoperoxidus gave six different patterns with EcoRI and five using the HindIII restriction enzyme.
Keywords: sekvenční homologie nukleových kyselin; Species Specificity; deoxyribonukleasa EcoRI; DNA bakterií; DNA, Bacterial; Deoxyribonuclease EcoRI; Ribotyping; druhová specificita; Deoxyribonuclease HindIII; deoxyribonukleasa HindIII; ribotypizace; Sequence Homology, Nucleic Acid; Enterococcus